2018
DOI: 10.3390/molecules23081917
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Pigments, Phenolics, and Antioxidant Activity of Chinese Jujube (Ziziphus jujuba Mill.) during Fruit Development

Abstract: Chinese jujube (Ziziphus jujuba Mill.) fruit are much admired for their unique flavor and high nutritional value. This study tracks changes in skin color and antioxidant activity over six stages (S1 … S6) of fruit development in two cultivars of jujube, ‘Junzao’ and the color mutant ‘Tailihong’. The study records the changing levels of chlorophylls, carotenoids, anthocyanins, and phenolic compounds during fruit development. Contents of chlorophylls, β-carotenes and anthocyanins decreased throughout the develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 42 publications
(49 reference statements)
5
40
0
1
Order By: Relevance
“…Fresh dates are usually harvested before they are fully ripe, in order to have the best quality, flavor and a good balance of sugar and acid content. Jujube fruit undergo significant texture and color changes during fruit development and postharvest ripening [16] The flavor and external attractiveness (color) are the most important quality attributes that determine consumer recognition and commercial value [13,17]. High-quality fruit typically have a deep red color, high sugar content and a balanced sugar-to-acid ratio [18,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fresh dates are usually harvested before they are fully ripe, in order to have the best quality, flavor and a good balance of sugar and acid content. Jujube fruit undergo significant texture and color changes during fruit development and postharvest ripening [16] The flavor and external attractiveness (color) are the most important quality attributes that determine consumer recognition and commercial value [13,17]. High-quality fruit typically have a deep red color, high sugar content and a balanced sugar-to-acid ratio [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The type and content of pigment determine the color of jujube fruit. The green and yellow colors of the fruit (epidermis) are derived from chlorophyll and carotenoids, while the red and reddish-purple mainly determined by the content and proportion of phenolic acid, flavonoids, flavanols and anthocyanins, which are associated with antioxidant activity and the medicinal properties of jujube fruit [ 16 , 21 – 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cosmulescu et al (2017) mentioned that jujube fruits are rich in bioactive compounds ( avonoids, carotenoids and anthocyanin) and can complement a healthy human diet. Shi et al (2018) concluded that changes in jujube fruit colour are associated with changes in antioxidant activity. Flavonoids and polysaccharides could contribute to the antioxidative e ect of jujube (Choi et al, 2011).…”
Section: Traditional Medicinal Uses and Potential Health Benefits Of mentioning
confidence: 99%
“…Samples (about 0.5 g) of jujube fruit skin were extracted with 5 mL of 0.1% HCl in methanol for 24 h, at 4 • C in the dark. After centrifuging at 12,000 rpm for 15 min, three replicates were used for each sample [29]. The total anthocyanin content (TAC) was measured by the pH differential method.…”
Section: Extraction and Analyses Of Total Anthocyaninsmentioning
confidence: 99%
“…In the color mutant jujube cultivar 'Tailihong' (TLH), the red color is due to anthocyanins [29]. Many studies have shown that bHLH transcription factors are involved in numerous physiological and biochemical processes in other plants.…”
Section: Introductionmentioning
confidence: 99%